T&C-CROP: representing mechanistic crop growth with a terrestrial biosphere model (T&C, v1.5) – model formulation and validation - J. Buckley Paules; S. Fatichi; B. Warring; A. Paschalis (Geoscientific Model Development)
Cropland cultivation is fundamental to food security and plays a crucial role in the global water, energy, and carbon cycles. However, our understanding of how climate change will impact cropland functions is still limited. This knowledge gap is partly due to the simplifications made in terrestrial biosphere models (TBMs), which often overlook essential agricultural management practices such as irrigation and fertilizer application and simplify critical physiological crop processes.